Dense Gas Towards the RX J1713.7–3946 Supernova Remnant - Maxted, N.; Rowell, G.; Dawson, B.; Burton, M.; Fukui, Y.; Lazendic, J.; Kawamura, A.; Horachi, H.; Sano, H.; Walsh, Andrew; Yoshiike, S.; Fukuda, T. (CSIRO, 2013)
We present results from a Mopra 7 mm-wavelength survey that targeted the dense gas-tracing CS(1-0) transition towards the young γ-ray-bright supernova remnant, RX J1713.7–3946 (SNR G 347.3−0.5). In a hadronic γ-ray emission scenario, where cosmic ray (CR) protons interact with gas to produce the observed γ-ray emission, the mass of potential CR target material is an important factor. We summarise newly discovered dense gas components, towards Cores G and L, and Clumps N1, N2, N3, and T1, which have masses of 1 – 104 M ☉. We argue that these components are not likely to contribute significantly to γ-ray emission in a hadronic γ-ray emission scenario. This would be the case if RX J1713.7–3946 were at either the currently favoured distance of ~1 kpc or an alternate distance (as suggested in some previous studies) of ~6 kpc. This survey also targeted the shock-tracing SiO molecule. Although no SiO emission corresponding to the RX J1713.7–3946 shock was observed, vibrationally excited SiO(1-0) maser emission was discovered towards what may be an evolved star. Observations taken 1 yr apart confirmed a transient nature, since the intensity, line-width, and central velocity of SiO(J = 1-0,v = 1,2) emission varied significantly.